AB0363 Rheumatoid arthritis and sickle cell disease: clinical, biological, radiological and therapeutics specific aspects. a retrospective observational study. (12th June 2018) - Stefko-Comte, L.; Eymard, F.; Habibi, A.; Galacteros, F.; Michel, M.; chevalier, X.; bartolucci, P.; guignard, S.
Abstract : Background: Thanks to medical advances in sickle cell disease (SCD) treatments, practitioners have to be aware of new comorbidities, as rheumatoid arthritis (RA). Methods: We conducted a retrospective, observational and monocentric study about clinical, biological and radiological specific aspects of RA in SCD patients and studied the impact of anti-rheumatic drugs, comparing the number of SCD flares occuring six months before/after their introduction, using medical files and phone inquiry. Results: Twenty-three patients were included in this study. Data about RA treatments and SCD flares could be collected for 15 patients. Middle age at RA diagnostic was 32.9 years-old, sexe ratio was 4.75F/1M. 74% of the patients were RF positive, 65% were ACPA positive. 74% of the patients had articular damages. Among them, 100% had severe carpite which appears to be the major radiological expression of RA in SCD patients, occuring sometimes without finger bone erosion. 100% received at least one specific drug for RA, 35% a biotherapy. There was no significant difference in the number of crisis before and after methotrexate introduction (p=1) or anti TNF alpha drugs (p=0.35 IC95% [−1.26;0.51]. Methotrexate had to be stopped for 3 patients because of acute chest syndrome, which did not occur with anti TNF. No infection was noticed. Conclusions: In conclusion, in SCD, RA occurs sooner in life course and to be more severe with a particular pattern: carpite and tarsite without finger bone erosion. The use of biotherapy appears to be safe, with a close monitoring. Disclosure of Interest: None declared